About Fluids Structure in Microchannels - Rudyak, V; Belkin, A; Egorov, V; Ivanov, D (The International Journal of Multiphysics, 2011)
The paper deals with molecular dynamics simulation of fluid flow characteristics in nanochannels. A new MD algorithm is developed to simulate plane flow with a pressure drop along the channel. Fluids of hard spheres and Lennard-Jones molecules are considered. Emphasis is on the study of the dependence of the hydraulic flow resistance on the fluid structure. An analysis was made of (i) the density distribution across and along the channel; (ii) radial distribution function of the fluid near the channel wall and in bulk; (iii) influence of the interaction law of the molecules with the wall; (iv) the dependence of the flow resistance coefficient on the Reynolds and Knudsen numbers.